Evaluation of Blended Learning Implementation which is Conditioned to Optimize the Mastery of Student Knowledge and Skills - Rozahi Istambul, Muhammad; Supriadi, Hari; ., . (International Journal of Engineering and Technology, 2018)
Learning process is part of the E-Procurement courses curriculum in Information Systems Study Program at Widyatama University. All this time, in the face-to-face method of learning process, students have not been able to optimize the mastery of knowledge and skills as expected. One of the things that the Information Systems Study Program did to optimize said mastery is applying the blended learning program in e-Procurement courses. This study uses mixed method evaluation approach in evaluating various stages of the process to implement a blended learning program. Meanwhile, the evaluation method used consists of 2 parts of the model namely 1) CIPP, an evaluation carried out on context, input, process, and product, 2) The Flashlight Triad, an evaluation of activities that utilize information technology online. As the final result of evaluating the implementation of blended learning based on observations and research that has been done, there is an optimization of the increase in mastery of students' knowledge and skills, after conducting various activities that are conditioned on face-to-face activities combined with online ones. The results of this evaluation mean that a well-conditioned blended learning program can influence students in terms of motivation, therefore mastering the knowledge and skills of a course can be optimized through the student learning experience.Â Â